Institutional Crisis in 21st Century Britain - Richards, David. author. aut Link
XV, 319 p.
Keywords: In 21st century Britain, a 'perfect storm' seems to have engulfed many of its institutions. This book is the first wholesale consideration of the crisis of legitimacy that has taken root in Britain's key institutions and explores the crisis across them to determine if a set of shared underlying pathologies exist to create this collective crisis.